ChemInform Abstract: Highly Enantioselective Intermolecular Hydroamination of Allylic Amines with Chiral Aldehydes as Tethering Catalysts. Issue 27 (13th June 2013) - MacDonald, Melissa J.; Hesp, Colin R.; Schipper, Derek J.; Pesant, Marc; Beauchemin, Andre M.
Abstract Both enantiomers of the products can be obtained using aldehydes (I) or (II) as catalysts.